Traces of German settlement in the modern-day cultural landscape of the Carpathians - Jordan Peter (Miscellanea Geographica: Regional Studies on Development)
Although German settlement in the Carpathians and their forelands declined to a minimum after World War II and again with the fall of Communism, its traces in the cultural landscape are still visible. This article investigates this fact, regarding the built cultural landscape, the linguistic landscape, and the aspect of landscape or regional identity rooted in a German past. Considering the modern Carpathian countries (Slovakia, Czechia, Poland, Ukraine, Romania), it starts by casting a light on the historical background of German settlement, followed by a glance at the current situation of Germans in the entire country, before focusing on German traces in the cultural landscape. It reveals that such traces are significant in areas that were populated by a German majority, or a larger share of Germans, up to World War II or even later, while, elsewhere, only scattered areas with German traces can be found. They are mostly well maintained, and frequently presented proudly – not least due to their function as tourist attractions, and because German emigrants and their descendants like to remain in contact with their former homes and visit them.